Portaria PGR/MPF nº 622, de 16 de julho de 2020 - Antonio Augusto Brandao de Aras (DOU, Brasília, DF, 20 jul. 2020. Seção 1, p. 137., 2020)
Altera e revoga trechos da Portaria PGR/MPF nº 350, de 28 de abril de 2017.